2017
DOI: 10.1016/j.jclepro.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and overcoming the barriers to structural steel reuse, a UK perspective

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(109 citation statements)
references
References 10 publications
3
106
0
Order By: Relevance
“…Enabling re-use provides considerable opportunities for steel and aluminium, given that many applications in building and transportation reach end-of-life not because they fail but because they are replaced for economic reasons. Barriers to re-use are typically not technical in nature but rather economic, such as lack of demand, traceability concerns and lack of supply chain infrastructure 91 . These systemic barriers need to be addressed to realize re-use potential through government leadership, education and information sharing.…”
Section: Longevity By Corrosion Protection Lifetime Extension and Reusementioning
confidence: 99%
“…Enabling re-use provides considerable opportunities for steel and aluminium, given that many applications in building and transportation reach end-of-life not because they fail but because they are replaced for economic reasons. Barriers to re-use are typically not technical in nature but rather economic, such as lack of demand, traceability concerns and lack of supply chain infrastructure 91 . These systemic barriers need to be addressed to realize re-use potential through government leadership, education and information sharing.…”
Section: Longevity By Corrosion Protection Lifetime Extension and Reusementioning
confidence: 99%
“…Growing academic attention has focused on the reuse of structural steel, thanks to steel's ubiquity, the significant environmental benefits that would arise from shortcutting recycling, and the intuitive feasibility of deconstructing and reusing these relatively high-value components. The literature identifies barriers and constraints; looks at cases of successful reuse to determine whether barriers are real or perceived; finds the economic case marginal; and proposes systemic and technical interventions to encourage a more effective supply chain [32,[66][67][68][69][70][71][72][73].…”
Section: Maintaining and Enhancing Utility Of Removals From Stockmentioning
confidence: 99%
“…It was noted, however, that the demand projects that can directly reuse components A detailed understanding of specific building components is not necessary for them to serve as feedstock for conventional recycling, because they will be returned to the state of raw material. This loss of specificity means that recycling can provide certainty over future (albeit lower) utility [68]. The utility of a specific reclaimed component, with its idiosyncrasies, is far less clear-cut.…”
Section: 'Where We Want To Be': a Triage Process To Support Reuse Rementioning
confidence: 99%
“…Only two studies were found that include ME strategies as part of forecasting exercises: studies performed by (Milford et al, 2013) and (IEA, 2015a). Other studies have examined strategies for recycling and re-use, employing metrics such as recycling rates (%), recycled content (%), scrap diversion (%); re-use rates (%), material intensities (tonnes per area, volume or service) (Allwood, 2014;Allwood et al, 2010b;Cullen and Allwood, 2012;Densley Tingley et al, 2017;Graedel et al, 2011). Embodied energy (GJ/t) and emissions (tCO 2 /t) also provide measures of cumulative savings, and are useful for making comparisons between ME options.…”
mentioning
confidence: 99%